Eksplorasi Implementasi Circle Time pada Sekolah Dasar yang Menerapkan Gerakan Sekolah Menyenangkan: Exploration of Circle Time Implementation in Elementary Schools of Gerakan Sekolah Menyenangkan - Rizqi Hanabella; Theresia Novi Poespita Candra (Jurnal Psikologi Teori dan Terapan, 2021)
This study aims to explore the effectiveness of circle time method as perceived by both teachers and students in the elementary schools that implement "Joyful Learning Movement” or Gerakan Sekolah Menyenangkan (GSM). The participants consisted of 22 students and 7 teachers from four elementary schools that implement GSM in Yogyakarta, Indonesia. A qualitative method was used, and data were collected using interviews and focus group discussions. Content analysis was used to analyze the data. The findings can be categorized in three themes, namely the benefits, supporting factors, and challenges of the circle time implementation. The benefits of circle time are indicated by the perceived improvement of children in terms of self-confidence, self-management, academic motivation, empathy, social skills, and active learning style. The supporting factors for circle time implementation as reported by participants include GSM itself, the flexibility in implementing circle time, and the teachers’ open-mindedness. For the challenging factors, participants suggest that limited time, available space, solid learning materials or curriculum, and students’ internal conditions are the main factors. The research findings can contributes to the better implementation of circle time in elementary schools. Keywords: Circle time, emotional-social learning, elementary school   Abstrak: Penelitian ini bertujuan untuk mengungkap efektivitas circle time di Sekolah Dasar yang mengikuti Gerakan Sekolah Menyenangkan (GSM) dari sudut pandang guru maupun murid. Partisipan penelitian terdiri atas 22 murid dan 7 guru dari empat sekolah dasar GSM di Yogyakarta, Indonesia. Penelitian ini menggunakan metode kualitatif dengan wawancara dan focus group discussion sebagai teknik koleksi data. Analisis konten digunakan untuk menganalisis data. Hasil penelitian menunjukkan manfaat, faktor pendukung, dan penghambat dalam penerapan circle time. Manfaat circle time ditunjukkan dengan persepsi subjek atas peningkatan kualitas siswa dalam kepercayaan diri, manajemen diri, motivasi akademik, empati, keterampilan sosial, dan gaya belajar yang lebih aktif. Sedangkan faktor pendukung circle time adalah GSM itu sendiri, fleksibilitas dalam pelaksanaan circle time, dan keterbukaan pikiran dari guru. Adapun faktor penghambat adalah keterbatasan waktu, tempat, materi pembelajaran dan kurikulum yang padat, serta faktor internal dari siswa sendiri. Hasil penelitian ini dapat memberikan wawasan yang berguna untuk sekolah dasar yang menerapkan circle time di sekolahnya.